Alkylpyrazines from Coffee are Extensively Metabolized to Pyrazine Carboxylic Acids in the Human Body. Issue 14 (5th June 2019) - Kremer, Jonathan I.; Pickard, Stephanie; Stadlmair, Lara F.; Glaß‐Theis, Anika; Buckel, Leon; Bakuradze, Tamara; Eisenbrand, Gerhard; Richling, Elke
Abstract : Scope: Coffee is a complex mixture of over 1000 compounds, including diverse heteroaromatic compounds such as alkylpyrazines. Little is known about the intake, metabolism, and bodily distribution of these compounds. Therefore, a human intervention study is conducted to investigate the excretion of alkylpyrazine metabolites in urine after the ingestion of brewed coffee containing alkylpyrazines. Methods and results: After consuming a diet without heat‐processed food, ten volunteers consumed 500 mL of freshly brewed coffee prepared from coffee pads, providing intakes of 2‐methylpyrazine (2‐MeP), 2, 5‐dimethylpyrazine (2, 5‐DMeP), and 2, 6‐dimethylpyrazine (2, 6‐DMeP) amounting to 17.2, 4.4, and 4.9 µmol, respectively. These alkylpyrazines are metabolized into the corresponding pyrazine carboxylic acids, namely pyrazine‐2‐carboxylic acid (PA), 5‐hydroxypyrazine‐2‐carboxylic acid (5‐OHPA), 5‐methylpyrazine‐2‐carboxylic acid (5‐MePA), and 6‐methylpyrazine‐2‐carboxylic acid (6‐MePA). In total, 64% of the ingested 2‐MeP is excreted as PA, as well as 26% as 5‐OHPA, while 91% and 97% of the ingested 2, 5‐DMeP and 2, 6‐DMeP are recovered as 5‐MePA and 6‐MePA, respectively, in urine samples collected after coffee consumption. Conclusion: This study provides evidence that alkylpyrazines are rapidly metabolized into the corresponding carboxylic acids and excreted via urine by humans, which is consistent with earlier rodent studies. Abstract : Alkylpyrazines are important flavor compounds in coffee. Methyl‐substituted pyrazines are metabolized to the corresponding carboxylic acid. This study focused on the renal excretion of these pyrazine carboxylic acids of the three most abundant alkylpyrazines in coffee. The urine samples of ten human participants, who consumed 500 mL of freshly brewed coffee, are analyzed by High‐performance liquid chromatography‐electrospray ionization tandem mass spectrometry (HPLC‐ESI‐MS/MS).